Optimasi Algoritme Genetika Untuk Memaksimalkan Laba Pembangunan Perumahan - Muhammad Faris Mas'ud; Imam Cholisoddin; Wayan Firdaus Mahmudy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Residence is a basic need. The main function of the residence is for a place to rest, security and family activities. Residential development highly demand along High population growth in the Malang city. when building homes, developers always prioritize the benefits in every construction without reducing the quality of the building. House construction requires human resources and some limited material, therefore genetic algorithms will be very helpful in terms of profit-seeking search. Based on several other Genetic Algorithm studies, this algorithm produces the expected solutions such as: hijab profit optimization, optimization of efficient distribution of goods and optimization of selection of targeted building workers. In accordance with the tests performed using data from Margobasuki Residence, obtained the optimal amount of benefits.